Exploring The Relationship between Self-Perceived Communication Competence and Speaking Anxiety in EFL Classrooms - Harahap, Afiyah Rizka; Evi Eliyanah; Maria Hidayati (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study explores the relationship between self-perceived communication competence (SPCC) and foreign language speaking anxiety (FLSA) among second-year English as a Foreign Language (EFL) students in an Indonesian university context. Using a quantitative correlational design, data were collected from students through the Self-Perceived Communication Competence (SPCC) scale and the Foreign Language Classroom Anxiety Scale (FLCAS). The focus of the study is on students’ experiences of speaking in classroom presentation settings. Statistical analysis reveals a significant negative correlation between SPCC and FLSA, indicating that students who perceive themselves as more communicatively competent tend to experience lower levels of speaking anxiety. These findings are consistent with previous research conducted in other EFL contexts and provide context-specific evidence from Indonesian higher education. The study highlights the importance of students’ self-perceptions in understanding speaking anxiety and suggests that EFL instructors should be attentive to learners’ confidence when designing speaking courses and activities. While limited by its correlational design, the study contributes empirical data that may inform further research on affective factors in EFL speaking classrooms.